Trigger Features for Conveying Facial Expressions: The Role of Segmentation. (November 2017) - Ramachandran, Vilayanur S; Chunharas, Chaipat; Smythies, Michael
Primates are especially good at recognizing facial expression using two contrasting strategies—an individual diagnostic feature (e.g., raise eyebrows or lower mouth corner) versus a relationship between features. We report several novel experiments that demonstrate a profound role of grouping and segmentation—including stereo—on recognition of facial expressions.